STUDENTS’ MATHEMATICAL CONNECTION PROCESSES IN PROBLEM POSING BASED ON REFLECTIVE-IMPULSIVE COGNITIVE STYLE - Annisa Nurul Hidayati; Ika Kurniasari (Program Studi S1 Matematika UNESA, 2021)
This study aims to describe the student’s mathematical connection processes in problem-posing reviewed by reflective-impulsive cognitive style. This research is descriptive qualitative with the chosen subjects are two female eleventh graders, one having a reflective cognitive style and one having an impulsive cognitive style, with both have a high mathematical ability. The subjects were chosen through analysis of math ability test (TKM), Matching Familiar Figure Test (MFFT), problem-posing test (TPM), and interview results. The result shows that: (1) the processes of mathematical connection of the student with reflective cognitive style in problem-posing are done consecutively. At the understanding information stage, the student identifies mathematics concepts, other science concepts, and their relationships with the real world. At the planning the problem-posing stage, the student plan to make a story problem with mathematics and other sciences concepts that have been identified. At the stage of making problems, the student does as planned and gives clear reasons for the use of information for the problem and the solution. At the re-checking stage, the student checked the completeness of the information that was used in the problem and also checked the correctness of the answer by proving it. (2) The processes of mathematical connection of the student with impulsive cognitive style in problem-posing are done dynamically and don’t up to the re-checking stage. At the stage of understanding information, the student couldn’t directly identify mathematics concepts and other sciences, and so started the processes again by reading information repeatedly, then continued to connect it with the real-world context. At the stage of planning the problem-posing, the student plans to make a story problem related to the mathematics and other sciences concepts that have been identified. At the stage of making problems, the student used all the information given and gave no apparent reason for it.